2010
DOI: 10.1111/j.1540-8159.2010.02915.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term RV Threshold Behavior by Automated Measurements: Safety is the Standpoint of Pacemaker Longevity!

Abstract: Despite technologic improvement in lead manufacturing, long-term increase of the RVPT occurs in about 13% of patients, possibly representing a serious safety issue in 3.7% when 2.5 V at 0.4 ms is exceeded. AVC algorithms can improve patients' safety by automatic tailoring of the pacing output to threshold fluctuations, while maximizing device longevity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…However, our follow-up lasted only 1 year and a further increase of atrial pacing threshold could occur as demonstrated by Biffi et al . [7] for ventricular threshold in 6.8% of patients beyond 1 year. In this event, the automatic adjustment of atrial amplitude could improve safety for patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, our follow-up lasted only 1 year and a further increase of atrial pacing threshold could occur as demonstrated by Biffi et al . [7] for ventricular threshold in 6.8% of patients beyond 1 year. In this event, the automatic adjustment of atrial amplitude could improve safety for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies regarding automated threshold testing review ventricular threshold testing. This was found to be safe and improve longevity . However, not much is published about automated atrial threshold testing, especially for Biotronik devices.…”
Section: Discussionmentioning
confidence: 99%
“…Automatic verification of capture and output management were a breakthrough innovation brought in clinical practice 25 years ago, that lead to increased patient safety and pacemaker (PM) longevity, with greater benefit at high pacing thresholds . Nowadays, these algorithms are available in PM and cardiac resynchronization therapy (CRT) devices, and have specificities in terms of beat‐to‐beat capture verification, evoked response (ER) detection vs conduction to another cardiac chamber, maximum capture threshold that can be managed by automated capture verification, possibility to work at different pulse widths or with differently manufactured leads in relation to their polarization (low vs high) .…”
mentioning
confidence: 99%